Iopamidol myelography induced status epilepticus - (:unkn) unknown (My University, 2009)
A forty-eight year old woman presented with convulsive status epilepticus and respiratory arrest 45 minutes after a lumbar myelogram with iopamidol. Status epilepticus in epileptic patients are very rare complication after myelography with iopamidol and to our knowledge status epilepticus in non epileptic patients have been previously reported only in one patient. Although it is a rare complication, physicians should be aware of this potential complication, myelogram should be performed in a full organized hospital. It will be better to observe patients carefully after the procedure.
Keywords: Electroencephalography; Iopamidol; Myelography; Status epilepticus